2003
DOI: 10.1007/s00428-003-0848-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of death in the early postoperative period following coronary artery bypass grafting for acquired heart disease. A clinicopathological study of 32 cases

Abstract: Criteria defined in this study may be useful in evaluations of causes of death after open heart surgery and may help to compare results in future series. Determination of the cause of death is important for the cardiac surgeon to reconsider indications and quality of surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Suture dehiscence usually occurs due to tissue tearing ; however, in our case, the tissue was intact and the suture was broken supporting the notion that dehiscence occurred due to suture rupture. As surgical sutures are made to withstand high physiologic pressures, one may assume there was either an intrinsic defect with the particular suture or a weakness was introduced during surgery.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Suture dehiscence usually occurs due to tissue tearing ; however, in our case, the tissue was intact and the suture was broken supporting the notion that dehiscence occurred due to suture rupture. As surgical sutures are made to withstand high physiologic pressures, one may assume there was either an intrinsic defect with the particular suture or a weakness was introduced during surgery.…”
Section: Discussionsupporting
confidence: 69%
“…In‐hospital mortality rates of CABG range from 1% to 3% and have remained steady despite the procedure being performed on progressively higher risk patients . Several autopsy studies have identified surgical complications as the cause of death in 27–43% of perioperative deaths, including anastomotic dehiscence in 3% of this population . Thus, the rate of death due to dehiscence is 0.09% (3% of 3%) of all CABG procedures or 1 per 1000 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A post mortem is done only in cases of death in theatre or in cases where the patient has not woken up. That being said, a routine post mortem is not always clarifying 29. The phase-of-care mortality analysis (POCMA) identifies an identifiable trigger for a fatal course 30.…”
Section: Discussionmentioning
confidence: 99%